SRITI Al-Fateh School Management System - Sofia Balqis, Mohamad Faisal (Universiti Malaysia Sarawak (UNIMAS), 2023)
In the age of up-to-date technology, nearly all industries are utilizing information systems with automated data for effective data retrieval, including the school industry. The school industry is utilizing ASIS to manage the school system. ASIS is useful for the school industry because it can lessen or block human errors and therefore enhance the process of managing the school system. This research is discussing the SRITI Al-Fateh school in Temerloh, Pahang. SRITI Al-Fateh wants to use the school management system for routine procedures in the school. Nevertheless, ASIS does not meet the requirement needed by SRITI Al-Fateh, including its software price. They have been utilizing a manual system which is utilizing a lot of paper and files to save their school records. Therefore, the objective of this project is to build a school management system for SRITI Al-Fateh. The primary goal of this project is to make sure a well-ordered way of keeping the school details and tracing the school fee history as well. In order to accomplish the goal, the requirements of users are gathered and studied, and analyses of the existing system have been made. The methodology utilized in this project is Rapid Application Development (RAD). Furthermore, the programming language utilized in building the system is HTML, CSS, JavaScript, PHP, and MySql in Notepad++. Closure and upcoming work will be covered at the finale of this project